Are validated patient-reported outcomes used on children in pediatric otolaryngology? A systematic review. (February 2018) - Wong, Kevin; Piraquive, Jacquelyn; Troiano, Chelsea A.; Sulibhavi, Anita; Grundfast, Kenneth M.; Levi, Jessica R.
Abstract: Objectives: Review the pediatric otolaryngology literature to 1) identify studies in which children completed patient-reported outcome (PRO) measures and 2) appraise the psychometric quality and validity of these PROs as they apply to pediatrics. Methods: In October 2016, a systematic review was performed by two reviewers on PubMed/MEDLINE and EMBASE for all otolaryngology-related studies that utilized PROs in children. Inclusion criteria included articles that required children (age<18) to complete PROs. Exclusion criteria included validation studies, reviews, and abstracts. Interreviewer agreement was determined using Cohen's kappa. Quality and rigor of validation testing for included PROs was determined using the COnsensus-based Standards for selection of health status Measurement Instruments. Results: Interrater agreement was very good (κ = 0.91; 95% CI, 0.85–0.98). Out of 316 articles retrieved, 11 met inclusion criteria. Eight PROs were identified. Six PROs were tested for validity and three of these PROs were tested for validity specifically within children. The most frequently utilized PRO was the Pediatric Rhinoconjunctivitis Quality of Life Questionnaire. Two studies (18.2%) utilized PROs within the scope of their validation. Seven studies (63.6%) used PROs outside the scope of their validation. Two studies (18.2%) used non-validated PROs. Conclusions: Patient-reported outcomes have become an integral part of research and quality improvement. There is a relative paucity of PROs directed towards children in pediatric otolaryngology and some studies utilized PROs that were not validated or not validated for use in this age group. Future efforts to design and validate more instruments may be warranted.